Life Cycle Assessment of Carbon Capture and Utilization for the Production of Large Volume Organic Chemicals - Rosental, Marian; Fröhlich, Thomas; Liebich, Axel (Frontiers in Climate, 2020)
The combination of carbon capture and utilization (CCU) and water electrolysis technologies can be used for the production of basic chemicals from carbon dioxide (CO2) and hydrogen. Here, we present a life cycle assessment (LCA) on a cradle-to-gate basis for the production of the following large volume organic chemicals: methanol, ethylene, propylene, benzene, toluene, and mixed xylenes. Investigated process chains comprise the following technologies: CO2 capture from an industrial point-source or from the atmosphere through direct air capture (DAC); alkaline water electrolysis for hydrogen production; methanol synthesis; methanol-to-olefins and methanol-to-aromatics synthesis including aromatics separation. Electricity is supplied by offshore wind turbines. The system boundary includes all relevant processes from cradle to gate. A scenario was set up by exchanging the background processes for the production of important infrastructure materials like aluminum, copper, steel, and concrete with future processes that are less resource intensive, less carbon intensive and include higher recycling rates (e.g. electric arc furnaces for steel production). LCA results show that the synthesis of the investigated chemicals from CCU processes will reduce greenhouse gas (GHG) emissions by 88–97 %, compared to fossil-based production routes, when electricity from offshore wind turbines is used. At the same time, other environmental impacts like eutrophication and ozone depletion will increase. The main contributors to the environmental impacts are the energy supply for water electrolysis and direct air capture. Replacement of all plants for the production of the investigated products in Germany with CCU processes would lead to a 2–7 % higher total primary energy demand for the whole country. At the same time, an overall reduction of the German GHG emissions by 6 % is achieved, when using offshore wind power for these processes only. The future scenario using improved background technologies leads to a further small reduction of GHG emissions and largely reduces other environmental impacts. We therefore identify the reduction of emissions through improved base material production processes and recycling of aluminum, copper, steel and concrete as main objectives to reduce negative impacts for the production of basic chemicals from CCU technologies.